2016
DOI: 10.1017/s1366728916000237
|View full text |Cite
|
Sign up to set email alerts
|

Early child second language acquisition: French gender in German children

Abstract: This study investigates the acquisition of grammatical gender in French by German L1 children (age of onset of acquisition (AO) 2;8-4,0). The analysis of spontaneous production data of 24 children gathered longitudinally and a gender assignment test administered to 8 of these children at ages 6;7-8;3 and to 9 children (AO 2,11-3;8) at ages 3;2-5;1 revealed that some of them resembled L1 learners whereas others behaved like adult L2 learners. The turning point is at around AO 3;6. AO is thus a crucial factor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 54 publications
3
13
1
Order By: Relevance
“…Investigating the effects of age on onset and of input in grammatical gender in Greek (early) and Dutch (very late), Unsworth et al (2014) found that amount of input was a predictive factor for the pattern attested in both Greek and in Dutch, whereas age of onset could explain the differences between 2L1 and successive bilinguals in Greek, but – as predicted by the timing hypothesis – not in Dutch. Likewise, the age of onset effects found by Meisel (2016) for gender in French, which is acquired early, are in line with the timing hypothesis. Furthermore, in a study with school-aged eL2 children acquiring English with a mean age of onset of 3 years, Chondrogianni and Marinis (2011) found effects of length of exposure rather than of age of onset for the acquisition of the late acquired structures wh-questions and passives.…”
Section: Factors Influencing Child Bilingual Acquisitionsupporting
confidence: 85%
“…Investigating the effects of age on onset and of input in grammatical gender in Greek (early) and Dutch (very late), Unsworth et al (2014) found that amount of input was a predictive factor for the pattern attested in both Greek and in Dutch, whereas age of onset could explain the differences between 2L1 and successive bilinguals in Greek, but – as predicted by the timing hypothesis – not in Dutch. Likewise, the age of onset effects found by Meisel (2016) for gender in French, which is acquired early, are in line with the timing hypothesis. Furthermore, in a study with school-aged eL2 children acquiring English with a mean age of onset of 3 years, Chondrogianni and Marinis (2011) found effects of length of exposure rather than of age of onset for the acquisition of the late acquired structures wh-questions and passives.…”
Section: Factors Influencing Child Bilingual Acquisitionsupporting
confidence: 85%
“…Sometimes, these findings are argued to be consistent with the notion of a sensitive period after which native-like acquisition gradually becomes impossible. Meisel's (2018) study is representative of this view. He studies similarities and differences between (2)L1 and cL2 acquisition, claiming that AoO is crucial in determining the course and result of early bilingualism.…”
Section: Introduction: Recent Developments In Early Bilingualismmentioning
confidence: 89%
“…As regards the role of AoA, Meisel (2018), examining grammatical gender in bilingual French/German children, found that children with an age-of-onset of acquisition before 3;6 produce the same constructions, proceed through the same developmental sequences, and attain the same grammatical system as monolingual children. For sequential bilingual children with a later AoA of the second language, this was not the case.…”
Section: Morphological Production In Bilingual Childrenmentioning
confidence: 99%